Reminiscences: periodical publication as an academic problem - Silveira, Paulo (PORTO ARTE: Revista de Artes Visuais, 2013)
This article offers some recollections about the implementation of support for Federal University of Rio Grande do Sul’s periodicals, a concomitant and following action to the consolidation of the editorial production of Brazilian universities from mid 80’s to late 90’s. Furthermore, it adds some remarks on the long, arduous preparation period of an academic journal, an adversity shared by many fields of knowledge, including the Visual Arts.